Right-Sided Pleural Effusion in a Critically Ill Stroke Patient - Bautista, Alexander (J Investig Med High Impact Case Rep, 2014)
Pleural fluid collections are common in those critically ill. We report the case of a left middle cerebral artery stroke patient who developed respiratory distress and required intubation and mechanical ventilation. Although the patient’s clinical status and oxygenation improved, there was persistence of right-sided opacity in the chest radiograph. Further workup proved a right-sided pleural effusion, which was drained and managed. Following extubation, a swallow study was ordered, which led to a fluoroscopic examination that demonstrated esophageal perforation. Thoracic surgery was consulted and did a primary repair of perforation and noted non–small cell carcinoma on the perforated site.